2018
DOI: 10.1111/jocs.13938
|View full text |Cite
|
Sign up to set email alerts
|

Permanent pacemaker implantation and paravalvular leak rates following sutureless aortic valve operations

Abstract: Background: Permanent pacemaker (PPM) implantation and paravalvular leak (PVL) rates after sutureless aortic valve replacement (SuAVR) vary widely. The aim of this metaanalysis was to examine the incidence of new PPM implantation and PVL after SuAVR.Methods: Studies evaluating PPM implantation and PVL rates after SuAVR were searched in Medline/PubMed, Ovid Journals, Clinicaltrials.gov, Cochrane central register of controlled trials and database. Studies with a sample size ≥10 were included in this analysis. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The PPM insertion rates from this current study are also much lower than those reported for TAVR (13.2%) and acceptable when compared to the 3.0% reported for conventional AVR in the meta-analysis by Cao et al (35). A recent meta-analysis (36) reported PVL incidence of 4.2% at 30-day and 5.9% at 1-year follow-up after TAVR. In the same study, incidence rates of severe PVL were 0.4% (30-day) and 0.5% (1-year follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…The PPM insertion rates from this current study are also much lower than those reported for TAVR (13.2%) and acceptable when compared to the 3.0% reported for conventional AVR in the meta-analysis by Cao et al (35). A recent meta-analysis (36) reported PVL incidence of 4.2% at 30-day and 5.9% at 1-year follow-up after TAVR. In the same study, incidence rates of severe PVL were 0.4% (30-day) and 0.5% (1-year follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…Concern exists regarding the increased incidence of conduction abnormalities following SURD-AVR (36,(47)(48)(49)).…”
Section: Pacemaker Implantationmentioning
confidence: 99%
“…Currently available sutureless prostheses have excellent hemodynamic performance and have been shown to reduce cross-clamp times but increase the risk of permanent pacemaker implantation (PPI) [1,2]. Although the risk of PPI is generally less than 5% with standard techniques, a recent meta-analysis documents a more than 2-fold increased risk of early PPI associated with sutureless valves [3]. This is of considerable concern because the presence of conduction abnormalities following percutaneous valve implantation increases the risk of late mortality [4].…”
Section: Invited Commentarymentioning
confidence: 99%